2010
DOI: 10.1186/1749-8090-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative intravenous fluid restriction reduces perioperative red blood cell transfusion in elective cardiac surgery, especially in transfusion-prone patients: a prospective, randomized controlled trial

Abstract: BackgroundCardiac surgery is a major consumer of blood products, and hemodilution increases transfusion requirements during cardiac surgery under CPB. As intraoperative parenteral fluids contribute to hemodilution, we evaluated the hypothesis that intraoperative fluid restriction reduces packed red-cell (PRC) use, especially in transfusion-prone adults undergoing elective cardiac surgery.Methods192 patients were randomly assigned to restrictive (group A, 100 pts), or liberal (group B, 92 pts) intraoperative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 14 publications
3
22
0
2
Order By: Relevance
“…The use of crystalloid cardioplegic solution and more flexible perioperative fluid therapy protocols is a predictor of haemodilution and increased transfusion demand. 25,26 In their meta-analysis, Russell et al 12 found that demand for blood was not significantly reduced when using albumin prime, although the heterogeneity of the studies included and differences in transfusion criteria could have affected the results. The use of ultrafiltration, however, particularly modified ultrafiltration techniques, succeeds in significantly reducing blood transfusion requirements to nearly 1 unit, similar to the findings of our study.…”
Section: Discussionmentioning
confidence: 98%
“…The use of crystalloid cardioplegic solution and more flexible perioperative fluid therapy protocols is a predictor of haemodilution and increased transfusion demand. 25,26 In their meta-analysis, Russell et al 12 found that demand for blood was not significantly reduced when using albumin prime, although the heterogeneity of the studies included and differences in transfusion criteria could have affected the results. The use of ultrafiltration, however, particularly modified ultrafiltration techniques, succeeds in significantly reducing blood transfusion requirements to nearly 1 unit, similar to the findings of our study.…”
Section: Discussionmentioning
confidence: 98%
“…However, even though transfusions are clearly necessary in many cases, blood product use has been associated with increased morbidity [4] and long-term mortality [3] in cardiac surgery, and therefore attempts to reduce blood transfusions may contribute to reduced complications and improved outcomes. Consequently, several measures have been evaluated in an attempt to reduce blood transfusions during cardiac surgery [12], including tolerating lower hemoglobin values [5] and restricting parenteral fluids in order to avoid hemodilution [16]. Studies evaluating the effectiveness of restrictive fluid administration strategies in mitigating the precipitous intraoperative hematocrit drop, rather than restrictive blood transfusion strategies, are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that, compared to liberal fluid administration, a restrictive parenteral fluid protocol significantly reduced intraoperative red blood cell (RBC) transfusions [17]. We also showed in a later RCT that restrictive fluid strategies may be more beneficial in patients prone to transfusion because of low preoperative hematocrit, female sex, or small BSA [16]. In both studies, re-infusion of washed blood from the thoracic cavities was used to reduce the need for transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations